Hubungan Karakteristik Individu terhadap Penilaian Kualitas Produk Apotek Rawat Jalan - Ade Nurma Ruditya; Djazuly Chalidyanto (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2015)
ABSTRACTPharmacy services in hospitals need special attention to achieve effectiveness and efficiency of quality dimensions. Achievement of customer satisfaction figures in Dr. Moewardi Pharmacy Hospital Surakarta didn't meet hospital standards that set in the amount of ≥ 80% over the years 2013 to 2014, especially in the outpatient pharmacy. The purpose of this research is to study the relationship between the individual factors of patient (age, sex, educational level, employment status, income level) to product quality assessment in an outpatient pharmacy. This research is an observational analytic with cross sectional study design. Data was collected by interview using a questionnaire. Analyzed using univariate and bivariate analysis. The Results of the analysis of the factor that were significantly associated with the assessment of product quality are age and employment status. The majority of respondents give high scores for product quality assessment. Individual patient factors associated with product quality assessment in outpatient pharmacies are age and employment status. Need to maintain the quality of existing products, and specifically to the dimensions of the product's features need to increase in order to better product quality.Keywords: pharmacy services, individual factors, products quality